Pathophysiology of Platelet Resistance to Anti-Aggregating Agents in Insulin Resistance and Type 2 Diabetes: Implications for Anti-Aggregating Therapy - Anfossi, Giovanni; Trovati, Mariella (Cardiovascular & Hematological Agents in Medicinal Chemistry, 2006)
The insulin resistance syndrome, which presents among its many facets obesity and type 2 diabetes mellitus, is a major risk factor for cardiovascular events. Thus, therapeutic guidelines recommend multifactorial treatment programs including, especially in the presence of type 2 diabetes, antiplatelet drugs. Few data, however, are available about the protective effect of antiplatelet therapy in both obese and type 2 diabetic patients. Furthermore, some reports showed a decreased sensitivity to the platelet antiaggregating effect of acetylsalicylic acid in diabetic patients. In the first part of this review, we focused our attention to alterations of platelets from insulin resistant subjects with or without type 2 diabetes, underlining that platelet hyperactivation is explained, at least in part, by: i) a reduced sensitivity to agents exerting an inhibitory modulation of platelet responses, ii) an altered intracellular milieu with elevated cytosolic Ca2+, iii) an enhanced thromboxane A2 synthesis, and iv) an increased number and/or function of GPIIb/IIIa complexes on platelet membranes. Furthermore, oxidative stress, which increases isoprostane production from arachidonic acid, may be involved in platelet hyperactivation, since isoprostanes activate platelets by interplaying with thromboxane receptors. These defects explain why antiplatelet therapy for both chronic atherosclerotic vascular disease and acute coronary syndromes should be specifically tailored in obese, insulin resistant subjects, especially in the presence of type 2 diabetes mellitus. Thus, in the second part of this review we carried out a critical overview of the clinical trials in subjects with metabolic syndrome and type 2 diabetes mellitus with or without macroangiopathy.
Keywords: insulin